Synthesis, Microstructural Characterization, Mechanical, Fractographic and Wear Behavior of Micro B4C Particles Reinforced Al2618 Alloy Aerospace Composites (Fracture and Structural Integrity, 2022)
In the current studies an investigations were made to know the effect of 63 micron sized B4C particles addition on the mechanical and wear behavior of aerospace alloy Al2618 metal composites. Al2618 alloy with different weight percentages (2, 4, 6 and 8 wt. %) of 63 micron sized B4C particles reinforced composites were produced by stir cast process. These synthesized composites were tested for various mechanical properties like hardness, compression strength and tensile behavior along with density measurements. Further, microstructural characterization was carried by SEM/EDS and XRD analysis to know the micron sized particles distribution and phases. Wear behavior of Al2618 alloy with 2 to 8 wt. % of B4C composites were studied as per ASTM G99 standards with varying loads and sliding speeds. By adding 63 micron sized B4C particles hardness, compression and tensile strength of Al2618 alloy was enriched with slight decrease in elongation. Further, wear resistance of Al2618 alloy was enriched with the accumulation of B4C particles. As load and speed on the specimen increased, there was increase in wear of Al2618 alloy and its composites. Various tensile fracture surface morphology and worn surface behavior was observed by SEM analysis.
Keywords: Al2618 Alloy; B4C; Microstructure; Mechanical and Wear Properties; Fractography; Worn Morphology